Knowledge, attitude, and practice of cancer patients regarding radiotherapy and radiation protection - Di Cui; Peng Wang; Lei Kong; Jidong Wang; Chuanhao Tang; Jun Liang (Frontiers in Oncology)
IntroductionThis study aimed to investigate the knowledge, attitude, and practice (KAP) of cancer patients regarding radiotherapy and radiation protection.MethodsA cross-sectional study was conducted between December 2023 and January 2024, at Peking University International Hospital, and included cancer patients through convenience sampling. Demographic characteristics and KAP scores were collected through distributed questionnaires.ResultsA total of 497 valid questionnaires were collected, with 252 (50.70%) completed by females. Of the respondents, 463 (93.16%) demonstrated awareness of the irradiation site for their treatment. Mean knowledge, attitude, and practice scores were 14.84 ± 4.99 (possible range: 0 - 28), 26.94 ± 3.63 (possible range: 8 - 40), and 25.24 ± 4.26 (possible range: 6 - 30), respectively. Correlation analyses revealed significant positive correlations between knowledge and attitude (r = 0.141, P = 0.002), as well as practice (r = 0.300, P < 0.001). Similarly, there was a correlation between attitude and practice (r = 0.279, P < 0.001). The path analysis revealed that knowledge was significantly associated with attitude (β = 0.142, P < 0.001) and practice (β = 0.202, P < 0.001). Similarly, attitude was associated with practice (β = 0.310, P < 0.001).ConclusionCancer patients exhibited inadequate knowledge, moderate attitudes and proactive practices towards radiotherapy and radiation protection. The positive correlations between knowledge and various factors, such as radiotherapy awareness, ionizing radiation understanding, and patient comprehensive scores, underscore the integral role of patient education in enhancing their approach to radiotherapy and radiation protection.